(untitled) (Proceedings of International Conference on Special Education, 2015)
Social-emotional competencies have been established as important predictors in children’s mental health, school readiness and academic success. Age and developmentally appropriate screening for preschool children is important for early detection of developmental delays and early intervention. The purpose of this study is to measure preschool children’s social emotional competencies based on the Malaysian context using MySECI (Malaysia Social Emotional Inventory), a social emotional competency inventory specially developed to provide parents, teachers and professionals with a standardized, norm-referenced, reliable and valid instrument. A pool of 50 items were created for MySECI, representing eight clusters of social emotional competencies in children: self-awareness, social awareness, self-management, relationship management, attachment, communication, responsible decision making and pro-social skills. This pilot study involved two public Annex preschools in town of Johor Bahru purposely selected with 49 preschool children as respondents. Results showed that My- SECI has high reliability index (Alpha Cronbach-Teachers .98 and Parents .95). Initial findings also showed that Teachers and Parents differ in their evaluation of their children’s SEC according to age and gender. But for the age criteria, the mean difference is slightly wider in comparison to gender. Therefore, MySECI is relevant in predicting children’s mental health, school readiness and academic achievement. Results from the study also showed that the inventory holds promise as a reliable and valid measure of social emotional competencies in young children for the Malaysian context.